Manufacture of a chitosan-based bioink with gelatin and hydroxyapatite and its potential application in 3D bioprinting - Sarahí Bautista Reberte; Esmeralda Zuñiga Aguilar; Solange Ivette Rivera Manrique; Carlos Alberto Martínez-Pérez (eXPRESS Polymer Letters)
Three-dimensional (3D) bioprinting is a technique currently used for creating tissue engineering scaffolds, using bioinks as the building blocks. These bioinks are composed of biomaterials that provide structural integrity and are synthesized from organic polymers to enhance biocompatibility with the printed constructs. In this study, a series of eleven chitosan-based bioinks were synthesized using the sol-gel technique, employing chitosan of low and medium molecular weight. Three bioink formulations were selected based on their viscosity characteristics and further enriched with gelatin and hydroxyapatite (HA) to enhance their mechanical properties. Characterization tests included Fourier-transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), scanning electron microscopy (SEM), and rheological assessments. Viscoelastic materials were obtained, and an experimental model was developed to optimize printing parameters, focusing on pressure and printing speed. Our findings indicate that a bioink formulation comprising a blend of medium and high molecular weight chitosan, supplemented with gelatin and hydroxyapatite, was found to be a promising approach for fabricating scaffolds for bone tissue repair.